The effect of AMF combined with biochar on plant growth and soil quality under saline-alkali stress: Insights from microbial community analysis - Yuqiang Wen; Ruotong Wu; Dandan Qi; Tianle Xu; Wei Chang; Kun Li; Xiaoxu Fang; Fuqiang Song (Ecotoxicology and Environmental Safety, 2024)
Arbuscular mycorrhizal fungi (AMF) and biochar application individually can enhance plant tolerance to saline-alkali stress and promote plant growth efficiency. However, little is known about the potential synergistic effects of their combination on improving plant growth and soil quality under saline-alkali stress. This experiment adopted the potted method to explore the effects of four treatments on switchgrass growth and soil quality: biochar (BC), Rhizophagus irregularis (Ri), biochar + Ri (BR) and a control without biochar or Ri (CK). Compared to the CK treatment, the switchgrass biomass increased by 92.4 %, 148.6 %, and 177.3 % in the BC, Ri, and BR treatment groups, respectively. Similarly, the rhizosphere soil quality index increased by 29.33 %, 22.7 %, and 49.1 % in the respective treatment groups. The BR treatment significantly altered the rhizosphere soil microbial composition and diversity. Notably, compared to the other treatments, the archaeal α-diversity in the BR group showed a significant decrease. BR treatment significantly increased the relative abundance of bacteria, fungi and archaea at the genus level (e.g., Bacillus, Trichome and candidatus_methanopenens). Network analysis showed that the complexity and closeness of interactions between different microbial taxa were stronger in the BC, Ri and BR treatments than in the CK treatment, with BR being the more prominent. In summary, biochar combined with Ri has a better effect on promoting the growth of switchgrass under saline-alkali stress, improving the quality of saline-alkali soil, and increasing soil microbial diversity. This study provides a new approach for the efficient development and utilization of saline-alkali land.